Resolving star and planet formation with ALMA. Issue Volume 14:Issue S345(2019) (August 2018) - Bjerkeli, Per; Harsono, Daniel; van der Wiel, Matthijs H. D.; Ramsey, Jon P.; Kristensen, Lars E.; Jørgensen, Jes K.
Abstract: Disks around young stars are the sites of planet formation. As such, the physical and chemical structure of disks have a direct impact on the formation of planetary bodies. Outflowing winds remove angular momentum and mass and affect the disk structure and therefore potentially planet formation. Until very recently, we have lacked the facilities to provide the necessary observational tools to peer into the wind launching and planet forming regions of the young disks. Within the framework of the Resolving star formation with ALMA program, young protostellar systems are targeted with ALMA to resolve the disk formation, outflow launching and planet formation. This contribution presents the first results of the program. The first resolved images of outflow launching from a disk were recently reported towards the Class I source TMC1A (Bjerkeli et al. 2016) where we also present early evidence of grain growth (Harsono et al. 2018).